2017
DOI: 10.3758/s13421-017-0741-0
|View full text |Cite
|
Sign up to set email alerts
|

Serial recall of colors: Two models of memory for serial order applied to continuous visual stimuli

Abstract: This study investigated the effects of serial position and temporal distinctiveness on serial recall of simple visual stimuli. Participants observed lists of five colors presented at varying, unpredictably ordered interitem intervals, and their task was to reproduce the colors in their order of presentation by selecting colors on a continuous-response scale. To control for the possibility of verbal labeling, articulatory suppression was required in one of two experimental sessions. The predictions were derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…We added these fillers to counter the argument that participants will adapt to unexpected syntactic information (i.e., start expecting unexpected information) and therefore not show prediction-consistency effects. Such adaptation-effects have been reported, albeit only for frequent repetition of an unexpected syntactic structure (see Fine, Jaeger, Farmer, & Qian, 2013 ; but see also a recent failure to replicate this type of adaptation effect, Stack, James & Watson, 2018 ), not for varied sentences structures as used in the current experiment. We have also added 60 relatively non-constraining stories to increase the variability of our materials and to make the ratio between the experimental and filler stories more similar to that of VB05.…”
Section: Methodssupporting
confidence: 43%
“…We added these fillers to counter the argument that participants will adapt to unexpected syntactic information (i.e., start expecting unexpected information) and therefore not show prediction-consistency effects. Such adaptation-effects have been reported, albeit only for frequent repetition of an unexpected syntactic structure (see Fine, Jaeger, Farmer, & Qian, 2013 ; but see also a recent failure to replicate this type of adaptation effect, Stack, James & Watson, 2018 ), not for varied sentences structures as used in the current experiment. We have also added 60 relatively non-constraining stories to increase the variability of our materials and to make the ratio between the experimental and filler stories more similar to that of VB05.…”
Section: Methodssupporting
confidence: 43%
“…Whereas the predicted effects have been observed in recognition tests (Morin et al, 2010) and some versions of reconstruction-of-order tests, they are conspicuously absent in immediate serial-recall tests (Lewandowsky et al, 2006;Nimmo & Lewandowsky, 2005Parmentier et al, 2006;Peteranderl & Oberauer, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…One prediction that could be challenged by existing data is that because resources recover over time, increasing the temporal gap before a study item should increase memory for that item. Most serial recall studies have not found evidence for this prediction (Brown & Lewandowsky, 2005;Lewandowsky, Brown, Wright, & Nimmo, 2006;Peteranderl & Oberauer, 2018). Nevertheless, such temporal isolation effects do occur in free recall tasks (Brown, Morin, & Lewandowsky, 2006), probed recognition tasks (Morin, Brown, & Lewandowsky, 2010), running memory span tasks (Geiger & Lewandowsky, 2008), unconstrained order reconstruction tasks (Lewandowsky, Nimmo, & Brown, 2008), and in one case, even in a forward serial recall task (Morin, Brown, & Lewandowsky, 2010) 24 .…”
Section: Temporal Isolation Effectsmentioning
confidence: 99%